Partnering with alumni for student and graduate success : final report. - Vanderlelie, Jessica (Australia. Dept of Education, 2019)
Every year thousands of students cross the graduation stage and make the transition to the world of work. As Australian universities and their staff beam with pride and reflect on a job well done, they hand responsibility for maintaining connection to each year’s 250,000 new graduates (QILT, 2018) to the able hands of our Alumni professionals. However, despite the latter’s best efforts, only 20% of graduates remain actively connected to their university. This National Learning and Teaching Fellowship supported universities to enhance student employability and graduate success in ways not previously explored in Australian or international Higher Education. The Fellowship matured from its original proposal, as the Fellow gained a deeper understanding of the political landscape of alumni engagement within the Australian and international context. The relationship the Fellow fostered with members of the Australian University Alumni Professionals Group (AUAPG) was invaluable, and was instrumental in broadening the Fellowship’s approach to improve its generalisability and maximise its impact and uptake by the sector. Importantly, the Fellowship deepened to consider alumni engagement across all disciplines, made explicit the role of alumni in supporting employability and addressed the tension between academic and alumni professionals working to engage alumni. During the Fellowship, Professor Vanderlelie connected deeply with the sector and engaged over 1900 individuals from 28 Australian and 27 international universities through research activities, presentations and workshops. The recommendations and frameworks developed during the Fellowship were informed through insights gathered from a strong research foundation that developed across the course of the Fellowship. The Fellow undertook a suite of semi-structured interviews (n=115) and focus groups (n=164 participants) with participants from 11 Australian and 27 international universities and surveys of students (n=288), Health Science academics (n=40) and Alumni professionals (n=23). Through these activities the Fellow explored the value that academic staff, students and Alumni professionals see in engaging graduates and identified the key challenges academic staff and Alumni professionals experience when working together and maintaining alumni communities. [Executive summary, ed]